Vascular Calcification in maintenance Hemodialysis patients in Pakistan – A single center Cross-sectional study - imtiaz, salman; Ahmed, Dr. Shahzad; Tariq, Dr. Sobia; Chughtai, Dr. Javeria; Saeed, Dr. Faiza; Memon, Shoukat; Alam, Dr. Ashar; salman, Beena (Pakistan Journal of Kidney Diseases, 2022)
Background: Cardiovascular disease is the most common cause of death in patients with CKD. The high cardiovascular risk may be due in part to excess vascular calcification. Our study aimed to determine the frequency of vascular calcification in maintenance hemodialysis patients. Material and Method: The study was conducted in the Department of Adult Nephrology, Indus Hospital, Karachi. This was a cross-sectional study. All patients who fulfilled the inclusion criteria were included in the study. After ethical approval and informed and written consent, a lateral abdominal x-ray was performed and reported according to the Kauppila score to reach the outcome i-e frequency of vascular calcification. Results: There was a total of 104 patients, of which 56(53.8%) were males. The mean age was 45.7± 14.2, with the minimum age being 20 years and the maximum 73 years. Most of our patients belonged to the middle socioeconomic group 96 (66.3%). The most prevalent cause of ESRD was DM in our patients 24 (23.1%), and almost all patients had AVF101 (97.1%) for HD access. Abdominal aortic calcification was present in 27 (26%) patients while ECHO revealed calcification in 10 (9.6%) patients. The degree of calcification according to the Kauppila score was mild to moderate in17(16.4%) and severe in 10(906%), while 77(74%) showed no calcification. The majority of patients were using calcium carbonate and calcium supplements 73 (70.2%). Conclusion: The frequency of vascular calcification in maintenance hemodialysis patients was low, it increases with the increase in age and no gender predominance was noted.